Custody Decisions in Social and Cultural Contexts: In-Depth and Focus Group Interviews with Nineteen Judges in Taiwan - Liu, Hung-En (Columbia Journal of Asian Law, 2004)
In 1996, Taiwan adopted the “best interests of the child” standard to substitute for the presumption of paternal custody in deciding child custody cases.’ Five years later, the researcher collected a sample of Taiwan’s court decisions on divorce cases involving custody disputes. By using the method of content analysis, the sample of cases was quantitatively analyzed in order to analyze how the courts applied the “best interests of the child standard.” The findings attest that Taiwan’s court decisions on child custody cases actually reflect many cultural ideas, such as stereotyped gender roles, family autonomy, a sense of “face,” all-or-none custody, and the tradition of parents’ long-term financial support for their children. The varying socio-economic climate of Taiwan across districts and the lack of public welfare programs also clearly affect judges’ custody decisions. Moreover, this study finds that since 1996, custody has been overwhelmingly awarded to mothers, whereas before 1996 fathers were favored by the courts. This article is a continuation of the previous study through interview research with judges. Following the quantitative examination of court decisions, the researcher found that it was necessary to conduct interview research with judges for several reasons. First, Taiwan’s court decisions do not always elaborate the judge’s reasoning in detail. Many commentators have harshly criticized the ambiguity and incompleteness of reasoning often seen in Taiwanese judges’ decisions. In fact, some judges often use “Li Gao” (model decision drafts) and just fit the names and facts of the cases into the drafts without changing the reasoning part while writing their decisions. Given that the reasoning of the decisions analyzed in the previous study was not complete in many cases, apparently we need to collect further data in order to reveal how judges actually applied the best interests of the child standard.